GENERAL PRINCIPLES OF THE EUROPEAN LEGAL SYSTEM IN TERMS OF THE TREATY OF LISBON - Florin STOICA (Challenges of the Knowledge Society, 2015)
Space widening European Community by joining several new states, reveals serious problems related to legal identity, social identity, sovereignty. The aim of this article is to explore some of the new principles created by the European law system, to show the necesity of creating an unique concrete system of law, in European community, with general principles. Even if, all the states in their accession process, knows about their required concessions, we can observe the difficulty of a new member in adapting the European principles established by treaties.